ANALISIS TINDAK TUTUR DALAM KUMPULAN CERPEN BERTANYA KERBAU PADA PEDATI KARYA A.A. NAVIS - Lina Merlina Dakhi (Universitas Nias Raya, 2025)
Early research was motivated by an initial study of the object of research in a collection of short stories asking buffalo on a pedati, that there are three types of speech acts, namely locutionary speech acts, illocutionary speech acts, and perlocutionary speech acts. Based on the formulation of the problem above, the objectives (a) To describe the locutionary speech acts in the collection of short stories asking Buffalo on a Pedati by A. A Navis. (b) To describe the illocutionary speech acts in the short story collection Ask the Buffalo on the Pedati by A. A Navis. (c) To describe the perlocutionary speech acts in the short story collection Bertanya Kerbau pada Pedati by A. A Navis. This research uses qualitative approach with description research type. Based on the results of research and discussion of speech acts in the collection of short stories asking the buffalo on the pedati by A.A Navis, the researcher concludes that in the speech acts in the collection of short stories asking the buffalo on the pedati by A.A Navis there are ten locutions, five illocutions and there are six perlocutions. In the speech acts in the collection of short stories asking the buffalo on the pedati by A.A Navis, there are 21 (twenty-one) speech acts. As for the suggestions in this study (1) Students should understand the values of life contained in every literary work and can help improve short story writing skills. (2) Future researchers should be able to develop this research with the scope of the research.